Exploring the perspectives of corporate governance and theories on Sustainability Risk Management (SRM) - Abdul Aziz, Nazliatul Aniza; Ab. Wahab, Norlida; Othman, Siti Norezam (Asian Economic and Social Society, 2015)
The motivation of this paper stems from the importance of observing good corporate governance by means of SRM approach to create sustainable value for corporate survival.This study explores the perspectives of corporate governance and underlying theories related to sustainability risk management (SRM). There is a growing concern that good corporate governance has an impact on SRM program.Good corporate governance influences companies to adopt sustainable business practices through a more holistic risk management approach in addressing both financial and non financial risks. Modern portfolio, stakeholder and legitimacy theories are the accepted paradigm in fostering a good corporate governance through the adoption of sustainable risk management in addressing sustainability risk.This paper adds to the literature by highlighting the importance of corporate governance through adoption of sustainable risk management practices in maximizing economic, environmental and social performance.